State Policy on Youth and Its Significance in The Context of New Uzbekistan - Doshhmuratova Gulbaxiram (Zien Journals, 2021)
The article analyzes the main directions of state youth policy in the new Uzbekistan. The role of raising the legal culture in the society in educating the youth has been revealed. A perfect man in the works of thinker’s special attention is paid to the historical and philosophical interpretation of the idea. The spiritual and legal basis for the upbringing of a harmoniously developed generation in the new Uzbekistan has been revealed.
Keywords: New Uzbekistan; state youth policy; talented youth; spiritual perfection